Umar farooq (may allah be pleased with him): the second caliph of islam - Khan, Nafisa; Rahman, Vinni (Goodword Books New Delhi, India, 2019)
"Umar Farooq (May Allah be Pleased with Him): The Second Caliph of Islam" is a biographical account of the life, leadership, and profound contributions of Umar ibn al-Khattab, showcasing his justice, wisdom, and unwavering dedication to Islam.